The within-host fitness of HIV-1 increases with age in ART-naïve HIV-1 subtype C infected children - Pradeep Nagaraja; Bindu P. Gopalan; Reena R. D’Souza; Debolina Sarkar; Niharika Rajnala; Narendra M. Dixit; Anita Shet (Scientific Reports, 2021)
Abstract As the immune system develops with age, children combat infections better. HIV-1, however, targets an activated immune system, potentially rendering children increasingly permissive to HIV-1 infection as they grow. How HIV-1 fitness changes with age in children is unknown. Here, we estimated the within-host basic reproductive ratio, R 0, a marker of viral fitness, in HIV-1 subtype C-infected children in India, aged between 84 days and 17 years. We measured serial viral load and CD4 T cell counts in 171 children who initiated first-line ART. For 25 children, regular and frequent measurements provided adequate data points for analysis using a mathematical model of viral dynamics to estimate R 0. For the rest, we used CD4 counts for approximate estimation of R 0. The viral load decline during therapy was biphasic. The mean lifespans of productively and long-lived infected cells were 1.4 and 27.8 days, respectively. The mean R 0 was 1.5 in children aged < 5 years, increased with age, and approached 6.0 at 18 years, close to 5.8 estimated previously for adults. The tolerogenic immune environment thus compromises HIV-1 fitness in young children. Early treatment initiation, when the R 0 is small, will likely improve viral control, in addition to suppressing the latent reservoir.